Benign ureteral polyps causing upper urinary tract obstruction - Hung, Nguyen Duy (Urol Case Rep, 2021)
Ureteral fibroepithelial polyps are benign, mesodermal neoplasms that can cause upper urinary tract obstruction. The preoperative diagnosis of this disease is challenging, but multidetector computed tomography (CT), particularly CT urography in the excretory phase, can be used to detect the features of ureteral polyps. We illustrated a case preoperatively diagnosed as upper ureteral tract obstruction due to ureteral tumor based on clinical presentation and CT imaging. However, the histopathological report revealed ureteral fibroepithelial polyps. Ureteral fibroepithelial polyps should be considered as a rare cause of urinary obstruction when the clinical presentation and imaging findings are atypical for more common etiologies.